Modality Analysis in Melania Trump’s and Ivanka Trump’s Campaign Speeches in Republican National Convention, July 19th, 2016 - Pionery, Hepie; Isti'anah, Arina (Universitas Sanata Dharma, 2017)
Style is a distinctive feature found in language use. One example of language use is a speech. In stylistics, the use of modality in a speech can reveal the speaker’s style. Subsequently, a style that is shown through the modality can reflect the speaker’s ideology. This study aimed to find out the ideology reflected by the modality of Melania Trump’s and Ivanka Trump’s campaign speeches. The speeches were delivered at the Republican National Convention last July 19th, 2016. There were two objectives discussed in this study. First is to find out the type of modality employed by Melania Trump and Ivanka Trump in their campaign speeches. Second is to reveal the ideologies reflected by the use of the modality. A stylistic approach was employed to discuss the types of modality to figure out the ideologies reflected. The data were taken by employing population study. From the analysis, it was found out that there were four types of modality employed by Melania Trump’s speech: inclination, obligation, potentiality and ability, and probability. In Ivanka Trump’s speech, there were five types of modality found: inclination, usuality, potentiality and ability, probability, and obligation. There were two ideologies reflected by the use of modality. The ideologies found in both speeches were similar. Those were commitment and self-promotion. The commitments were proved by the existence of inclination, while self-promotion is proven by the existence of potentiality and ability, and usuality types of modality. Keywords: speech, modality, ideology, stylistics